Redistribution of critical drugs in shortage during the first wave of COVID-19 in France: from operating theaters to intensive care units - Claire Chapuis; Rémy Collomp; Laura Albaladejo; Hugo Terrisse; Stéphane Honoré; Jean-Luc Bosson; Pierrick Bedouch; Pierre Albaladejo (Taylor & Francis Group, 2022)
Background Tension in the supply of highly consumed drugs for patients with COVID-19 (propofol, midazolam, curares) led the French government to set up a centralized supply of hospitals with distribution based on the number of resuscitation beds in March 2020. The French Societies of Clinical Pharmacy and of Anesthesia and Critical Care aimed to evaluate the changes in total needs and the distribution between anesthesia and critical care activities (CCU), to prepare resumed surgical activity. Methods National declarative survey among pharmacists, via an online form (SurveyMonkey®), was conducted in April and May 2020. The analysis focused on quantities dispensed during the whole year 2019, and March and April of year 2019 and 2020 for the drugs subject to quota, and on their distribution in CCU and operating theaters. Results For the 358 establishments (47% public, 53% private), dispensations in CCU in March 2020 compared to March 2019 increased, respectively: propofol (+81%), midazolam (+125%), cisatracurium (+311%), atracurium (+138%), rocuronium (+119%); and decreased for anaesthesia: propofol (−27%), midazolam (-10%), cisatracurium (−19%), atracurium (−27%), rocuronium (+16%). Conclusions Variation of dispensations between CCU and others was directly related to the increase of COVID patients in CCU and the decrease in surgical activity. Each establishment could receive up to five or six different presentations and concentrations, leading to a major risk of medication error. This collaborative national survey provided accurate data on the drugs' usual consumption. This work emphasized the need for a strong collaboration between pharmacists and anesthesiologists and intensive care physicians. It was further used by the Health Ministry to adjust the drug distribution.